Cortical Gyrification and Cognitive Decline in the Human Brain With Type 2 Diabetes Mellitus - Weiye Lu; Yuna Chen; Zidong Cao; Zhizhong Sun; Wenbin Qiu; Limin Ge; Xin Tan; Yi Liang; Shijun Qiu (Brain and Behavior)
ABSTRACT Introduction Type 2 diabetes mellitus (T2DM) is linked to abnormal brain structure and cognitive dysfunction. However, there is a lack of studies conducted to assess the impact of diabetes on cortical gyrification and cognition. The aim of this cross‐sectional study was to assess the potential negative effects of glucose metabolism levels on cognition and cortical gyrification in T2DM. Methods The current study comprised 83 patients with T2DM and 60 individuals with normal glucose metabolism (NGM). The calculation of the local gyrification index (LGI) was performed utilizing the FreeSurfer software. Subsequently, between‐group differences were examined through the utilization of analysis of covariance. Multivariable linear regression and mediation models were employed to investigate the relationships among LGI, glucose metabolism and cognition. Results Our study found that the mean LGI of the entire brain in individuals with T2DM was lower than that of NGM, and these significant hypogyria were mainly located in the bilateral temporal lobes, including the left superior temporal cortex, left transverse temporal cortex, and bilateral temporal pole, with the greatest effect size in the left temporal pole (p = 5.7×10−7, Cohen's f2 = 0.169). In addition, the relationship between fasting blood glucose and working memory was mediated by the LGI in the right temporal pole. Conclusion Our experiment suggests that the decreased LGI in the right temporal pole explains poorer working memory performance in patients with T2DM.